Immunotherapy with the saponin enriched-Leishmune (R) vaccine versus immunochemotherapy in dogs with natural canine visceral leishmaniasis - Borja-Cabrera, G. P.; Santos, F. N.; Santos, F. B.; Trivellato, Fernando Antonio de A.; Kawasaki, Jarbas Kiyoshi A.; Costa, Andreia Cerqueira; Castro, Tatiana; Nogueira, F. S. [UNESP]; Moreira, M. A. B.; Luvizotto, M. C. R. [UNESP]; Palatnik, M.; Palatnik-de-Sousa, C. B. (Elsevier B.V., 2010)
Leishmune (R), the first licensed vaccine for prophylaxis against canine visceral leishmaniasis (CVL) and is also immunotherapeutic when used with double saponin adjuvant concentration. The Leishmune (R) therapeutic vaccine was assessed for immunotherapy (IT) in 31 infected dogs and for iminunochemotherapy (ICT) in combination with allopurinol or amphotericinB/allopurinol, in 35 dogs Compared to infected untreated control dogs, at month 3. both treatments increased the proportion of dogs showing intradermal response to Leishmania antigen to a similar extent (from 8 to 67%, in the IT and to 76%, in the ICT groups), and conversely reduced from 100 to 38% (IT) and to 18% (ICT) the proportion of symptomatic cases, from 54 to 12% (IT) and to 15% (ICT) the proportion of parasite evidence in lymph nodes and from 48 to 19% (IT) and 12% (ICT) the proportion of deaths, indicating that the immunotherapy with enriched-Leishmune (R) vaccine promotes the control of the clinical and parasitological signs of CVL rendering most dogs asymptomatic although PCR positive. By month 8, negative lymph node PCR results were obtained in 80% of the ICT-treated dogs, but only in 33% of the IT group (p = 0.0253), suggesting that the combination of additional chemotherapy with Leislimune (R)-enriched saponin vaccination abolished, not only the symptoms but also the latent infection condition, curing the dogs. The animals were followed up until 4.5 years after the beginning of the experiment and. compared to the untreated control group at month 3 (12/25 dogs; 48%). a decrease in the rate of CVL deaths was only seen after ICT treatment (7/35 dogs; 20%; 0 0273) but not after IT treatment (10/31 dogs; 32%; p = 0.278), pointing out an additional advantage of the ICT treatment with the enriched-Leishmune (R) in the control and cure of CVL (C) 2009 Elsevier Ltd All rights reserved
Keywords: Canine visceral leishmaniasis; Kala-azar; Leishmania chagasi; Leishmune (R); Saponin; Immunotherapy; Immunochemotherapy; Allopurinol; Amphotericin B